Chapter Il Progetto Sperimentale di Tirocinio Diretto Digitale Integrato - Grilli, Antonella (Strumenti per la didattica e la ricerca, 2022)
The integrated digital direct internship (TDDI) represents a new and important method of internship of an experimental nature that began in December 2020, in collaboration with the Regional School Office for Tuscany, to guarantee all students to live a fundamental pre-professional experience, also through virtual and digital methods, thus allowing to expand and enrich training opportunities.